TANGGUNG JAWAB DIREKTORAT JENDERAL KEKAYAAN INTELEKTUAL TERHADAP PENDAFTARAN MEREK DENGAN MELAKUKAN PERBUATAN PASSING OFF - Muhammad Rizky Aufananto (2021)
This study aims to determine the responsibility of the Directorate General of Intellectual Property for trademark registration by doing the act of passing off and to find out the legal protection for well-known trademark holders who have not registered against the act of passing off. The research method used in this research is normative juridical research which is carried out by examining library materials or secondary data only and using a statutory approach and a case approach. The data collection technique is done through literature study and the method used in analyzing the collected data is qualitative analysis. The results show that the DGIPT's responsibility for the registration of marks indicated by the act of passing off, which includes before the mark is registered, if in the results of the examination there is an indication that the registered trademark has committed an act of passing off, the registration must be rejected and its registration not accepted by DGIP And another responsibility of the DGIP is when after the mark is registered and a claim for cancellation of the mark by the original trademark holder is filed with the Commercial Court. In this case, DGIP has the responsibility as the executor of the Court Decision to cancel the registration of the mark. Furthermore, well-known trademark holders who have not registered their trademarks in Indonesia will still be given legal protection from any trademark registration indicated as having carried out an act of passing off by filing a lawsuit against the registered mark as mentioned in Article 76 Paragraph (1). The provisions in Article 76 Paragraph (2) and (3) state that a well-known trademark holder who has not been registered can file a lawsuit for cancellation of a registered mark (after submitting an application to the DGIP) to the Commercial Court.